Oct-2 facilitates functional preinitiation complex assembly and is continuously required at the promoter for multiple rounds of transcription. - Arnosti, D N (1993)
Octamer factor 2 (Oct-2, OTF-2, NF-A2) is an 'upstream' promoter factor that binds to the octamer motif (ATGCAAAT) implicated in control of immunoglobulin gene transcription in B-lymphocytes. We have studied the role of Oct-2 in the process of transcription initiation in vitro using both nuclear extracts and purified basal transcription factors. Oct-2 specifically stimulates transcription from octamer-containing promoters in both systems. Thus, Oct-2 is a 'true activator', rather than merely an 'anti-repressor' counteracting the effect of histones. In order-of-addition experiments, Oct-2 is required early, together with TFIID, to allow formation of a preinitiation complex. Oct-2 cannot functionally interact with cloned TATA binding protein (TBP) but rather requires 'coactivators' found in the TFIID fraction. In single-round transcription experiments, early competition for Oct-2 by an octamer oligonucleotide is deleterious, but no effect is seen after assembly of a complete preinitiation complex. However, for multiple rounds of transcription, Oct-2 is continuously required at the promoter; this result argues against a 'hit-and-run' mechanism whereby the activator becomes dispensible after organizing a TFIID-promoter complex. In agreement with our previous studies in vivo, the N-terminal glutamine-rich activation domain of Oct-2 is required for full activity in vitro, indicating that this domain directly interacts with basal transcription factors.